Use of natural zeolites as ASR inhibitor in basaltic rocks - Locati, Francisco (2015)
The capacity of a natural zeolite from the province of La Rioja (Argentina) to inhibit the alkali-silica reaction (ASR) was studied. The pozzolanic material corresponds to a mixture of clinoptilolite zeolite with minor gypsum, quartz and feldspar discarded in spoil heaps in a quarry. An alkali-reactive basaltic aggregate from a quarry in the Argentine Mesopotamia region was used for the study. Two series of tests according to the accelerated mortar bar method (IRAM 1674) were carried out. One set with 0% (control specimen), 10%, 15% and 20% replacement of cement by natural zeolite and another with the same percentages but using milled zeolite. To monitor the reaction process, mortar bars were studied after the test by stereomicroscopy, polarizing microscopy and SEM-EDS. After 16 days of testing, a reduction in expansion (~42 %) was detected in the mortars with 20% replacement by natural zeolite. However, their behaviour was still reactive. On the other hand, the mortars with 20% replacement by milled zeolite produced a 90% reduction in expansion at 16 days, below the limit prescribed by the standard. A simple milling process transforms this material into a good pozzolanic material inhibiting the alkali-reactivity of basaltic aggregates.